Pengaruh Penggunaan Pupuk Majemuk (NPK) Terhadap Produksi Kedelai - Supeki Supeki (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
In soybean cultivation the use of fertilizers is needed in both single and compound forms. Given that fertilizer prices are quite expensive; their use must be efficient. Problems faced where farmers are still often not cultivating soybean plants. Though soybean plants require high N, P, and K nutrients. The research was carried out in the experimental gardens of the Agricultural Training Center for the Food and Horticulture Crops of Papua Province in May to August 2016. The data analysis was done using tabulation and processed using the program Excel. Planting Anjasmoro variety of soybeans was done using NPK compaction 15-15-15 + TE compound DGW production from PT. Hextar Fertilizer Indonesia with a dose of 140.06 kg / ha can produce an average plant height of 86.85 cm and yields with a production of 3.83 tons / ha and a weight of 100 seeds is 17 gr / 100 seeds. This fact shows that the use of NPK compound fertilizer can be recommended as a supplementary fertilizer to increase soybean growth and proudness. However, NPK compound fertilizer can also be used as a basic fertilizer if the availability of a single fertilizer N, P, and K is not available or more expensive with regard to the adequacy or dosage of its use.